4x-(4*3x)=4

Simple and best practice solution for 4x-(4*3x)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-(4*3x)=4 equation:


Simplifying
4x + -1(4 * 3x) = 4

Multiply 4 * 3
4x + -1(12x) = 4

Remove parenthesis around (12x)
4x + -1 * 12x = 4

Multiply -1 * 12
4x + -12x = 4

Combine like terms: 4x + -12x = -8x
-8x = 4

Solving
-8x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-8'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 5n+4=20 | | 10(10+x)=20 | | n^6=90 | | 7(y-5)=-3(4+y) | | (x+4)(x-17)=x | | 16y+32=48 | | 34-2(4+5)= | | 5x-7=2x-6 | | 7x+14=28 | | 6y+18=24 | | 12x+1=91-6x | | 27x-4=122+6x | | 4y-12=20 | | x^3-6x^2-36x-40=0 | | 22x-7=209-2x | | 7a-14=21 | | 4x-8=52-2x | | 7a+14=21 | | 14x-7=213-8x | | 3x+4y=-3 | | 8x+1=121-4x | | 14x-4=12-2x | | x-4/7=3/7 | | -3.5=m-2.5 | | 4a+13=21 | | 3*x^3-9*x^2-9x+26=0 | | 4t-3.5t=1 | | n+7=28 | | -(2x-6)+(-x+7)=7 | | 3p^2+3p-60= | | x^2-3x+2=6 | | 2(4t-1)-4(1-t)=12t-6 |

Equations solver categories